2019
DOI: 10.1038/s41467-019-08493-7
|View full text |Cite
|
Sign up to set email alerts
|

Combined loss of LAP1B and LAP1C results in an early onset multisystemic nuclear envelopathy

Abstract: Nuclear envelopathies comprise a heterogeneous group of diseases caused by mutations in genes encoding nuclear envelope proteins. Mutations affecting lamina-associated polypeptide 1 (LAP1) result in two discrete phenotypes of muscular dystrophy and progressive dystonia with cerebellar atrophy. We report 7 patients presenting at birth with severe progressive neurological impairment, bilateral cataract, growth retardation and early lethality. All the patients are homozygous for a nonsense mutation in the TOR1AIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 51 publications
(68 reference statements)
5
58
2
Order By: Relevance
“…Here, we present two unrelated individuals with striking clinical similarities bearing biallelic loss-of-function variants in TOR1AIP1 affecting both LAP1 isoforms. In comparison to the abovementioned study (Fichtman et al 2019), one individual survived until 16 years of age and the other is alive at 34 years of age, respectively, and they were affected by multisystem anomalies and progeroid appearance that progressed with age. Moreover, we present the cellular characterization of primary fibroblasts of one of the affected individuals.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Here, we present two unrelated individuals with striking clinical similarities bearing biallelic loss-of-function variants in TOR1AIP1 affecting both LAP1 isoforms. In comparison to the abovementioned study (Fichtman et al 2019), one individual survived until 16 years of age and the other is alive at 34 years of age, respectively, and they were affected by multisystem anomalies and progeroid appearance that progressed with age. Moreover, we present the cellular characterization of primary fibroblasts of one of the affected individuals.…”
Section: Introductionmentioning
confidence: 79%
“…(Ghaoui et al 2016). Furthermore, a recent study identified a homozygous Palestinian founder variant, p.(Arg321*), in seven individuals from five likely related families affected by early onset multisystem anomalies with progeroid appearance and lethality in the 1st decade of life (Fichtman et al 2019). Only those bearing the p.(Arg321*) had a loss of both LAP1B and LAP1C protein isoforms.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, many of these mutations map to regions on TorsinA at the inter-subunit interface, suggesting they perturb Torsin/Torsin or Torsin/cofactor binding [4,12,67]. Supporting the idea that interrupting the Torsin/cofactor interaction is detrimental are reports of patients with mutations in the LAP1 gene, TOR1AIP1, who display dystonic-like symptoms [15,68], cardiomyopathy [14,15,68,69], deafness [14,68], and muscular dystrophy [16,69] (Figure 2A). Although many of these phenotypes arising from the TOR1AIP1 mutation are distinct from those observed in patients with TOR1A mutations, a subset of TOR1AIP1 patients experience dystonic symptoms similar to those presented by DYT1 dystonia (TOR1A mutation) patients.…”
Section: Torsin Assemblies and Dystonia Movement Disordersmentioning
confidence: 86%
“…Further underscoring the importance of the Torsin/cofactor assembly during development is a recent report describing a mutation within the LAP1 gene TOR1AIP1 that results in a loss of LAP1 expression in patients with dystonia-like symptoms, along with other pathology (see below, Figure 2A,B) [14]. In fact, several disease-associated mutations have been reported for LAP1 ( Figure 2A,B) [14][15][16] but none for LULL1, suggesting critical roles for the Torsin/LAP1 complex at the NE [14][15][16]. Torsins are implicated in multiple essential cellular processes at the nuclear envelope (NE) and endoplasmic reticulum (ER).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation